Death and literature: Different approaches, from simplicity to obscurity - John Skelton (Mètode Science Studies Journal: Annual Review)
This study looks briefly at a range of ways in which writers have approached the concept of death, from expressions of personal grief, through to the ways in which attitudes to death represented in a culture are also picked up and used by writers from the culture concerned. Writers considered are mostly (but not all) from the English and Spanish language traditions, and in particular Seamus Heaney, Thomas Hardy, Miguel de Cervantes and Federico García Lorca. The point is made that not all writing about death is centred on death as a source of personal grief, though a great deal is. Also considered is the way in which some writing about death is transparent, and in a sense overtly simple, while other writing is less so, and may even seem obscure.